Dexamethasone Treatment Limits Efficacy of Radiation, but Does Not Interfere With Glioma Cell Death Induced by Tumor Treating Fields - Linder, Benedikt; Schiesl, Abigail; Voss, Martin; Rödel, Franz; Hehlgans, Stephanie; Güllülü, Ömer; Seifert, Volker; Kögel, Donat; Senft, Christian; Dubinski, Daniel (Frontiers in Oncology, 2021)
Purpose: Dexamethasone (Dex) is the most common corticosteroid to treat edema in glioblastoma (GBM) patients. Recent studies identified the addition of Dex to radiation therapy (RT) to be associated with poor survival. Independently, Tumor Treating Fields (TTFields) provides a novel anti-cancer modality for patients with primary and recurrent GBM. Whether Dex influences the efficacy of TTFields, however, remains elusive. Methods: Human GBM cell lines MZ54 and U251 were treated with RT or TTFields in combination with Dex and the effects on cell counts and cell death were determined via flow cytometry. We further performed a retrospective analysis of GBM patients with TTFields treatment +/- concomitant Dex and analysed its impact on progression-free (PFS) and overall survival (OS). Results: The addition of Dex significantly reduced the efficacy of RT in U251, but not in MZ54 cells. TTFields (200 kHz/250 kHz) induced massive cell death in both cell lines. Concomitant treatment of TTFields and Dex did not reduce the overall efficacy of TTFields. Further, in our retrospective clinical analysis, we found that the addition of Dex to TTFields therapy did not influence PFS nor OS. Conclusion: Our translational investigation indicates that the efficacy of TTFields therapy in patients with GBM and GBM cell lines is not affected by the addition of Dex.